Child Care Subsidies, Quality of Care, and the Labor Supply of Low-Income, Single Mothers - Berger, Mark C.; Black, Dan A. (The Review of Economics and Statistics, 1992)
Mark C. Berger, Dan A. Black, Child Care Subsidies, Quality of Care, and the Labor Supply of Low-Income, Single Mothers, The Review of Economics and Statistics, Vol. 74, No. 4 (Nov., 1992), pp. 635-642